Nanoteknologi Farmasi Ziprasidone Nanocrystals By Wet Media Milling Followed By Spray Drying AndLyophilization: Formulation And Process Parameter Optimization - Mutiara Deas Tantia; Nahla Akila Fikria; Vio Agister Risanl (Pt. Anagata Sembagi Education, 2024)
lyophilisation. The research methods used include the preparation of Ziprasidone nanosuspension using size reduction technique, optimisation of process parameters, formulation of media milling technique, and evaluation of the physical stability of the optimised nanosuspension. The results of this study are expected to provide a better understanding of the use of nanocrystals in improving the solubility and bioavailability of drugs with poor solubility such as Ziprasidone. In addition, this study is also expected to provide new insights into the use of spray drying and lyophilisation technologies to improve the physical stability of drug nanosuspensions. In conclusion, this study highlights the importance of using nanocrystals in improving the solubility and bioavailability of drugs with poor solubility such as Ziprasidone. Spray drying and lyophilisation methods have been shown to be effective in improving the physical stability of drug nanosuspensions. This research can serve as a foundation for the development of more effective drug formulations that can be used in wider clinical applications.